2021
DOI: 10.3389/fpsyg.2021.693644
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Relationship Between Entrepreneurship and Psychological Characteristics, and Corporate Social Responsibility Under Marketization

Abstract: The present work aims to explore how and to what extent ventures can bear social responsibilities due to their increasingly important role in social and economic activities. Here, the correlation between entrepreneurship and psychological characteristics of entrepreneurs, and corporate social responsibility is analyzed from the perspective of entrepreneurial entrepreneurs based on marketization theories of enterprise activities. The β value of entrepreneurship in corporate social responsibility is obtained as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(30 reference statements)
1
2
0
Order By: Relevance
“…In accordance with this result, previous studies have demonstrated the importance of CSR in improving corporate sustainability performance and promoting organizational development (Crișan-Mitra et al, 2020;May et al, 2021;Vătămănescu et al, 2021). Besides, the study extends understanding of the antecedents and consequences of CSR (Pasricha et al, 2018;Memon et al, 2021;Shen et al, 2021;Zhao et al, 2021). Furthermore, it is very interesting that the mediating role of CSR connects upper echelons theory and SIP theory.…”
Section: Discussionsupporting
confidence: 82%
“…In accordance with this result, previous studies have demonstrated the importance of CSR in improving corporate sustainability performance and promoting organizational development (Crișan-Mitra et al, 2020;May et al, 2021;Vătămănescu et al, 2021). Besides, the study extends understanding of the antecedents and consequences of CSR (Pasricha et al, 2018;Memon et al, 2021;Shen et al, 2021;Zhao et al, 2021). Furthermore, it is very interesting that the mediating role of CSR connects upper echelons theory and SIP theory.…”
Section: Discussionsupporting
confidence: 82%
“…Recognizing the potential introduction of estimation bias attributed to the omission of pertinent variables, this study has undertaken a comprehensive robustness assessment through the introduction of control variables. Prior scholarly endeavors have underscored the influence exerted by entrepreneurs’ characteristics upon a company’s engagement in social responsibility activities ( 48 ). As such, to comprehensively address potential confounding factors, this analysis incorporates four control variables that encapsulate entrepreneurs’ attributes.…”
Section: Resultsmentioning
confidence: 99%
“…There is empirical evidence that research and development (R&D) expenditures are correlated with CSR choice ( Padgett and Galan, 2010 ; Li et al, 2021 ). Similarly, the degree of marketization, the ratio of independent directors, and the management expense ratio are related to CSR investment ( Flammer, 2015 ; Ardito et al, 2021 ; Shen et al, 2021 ). We additionally include regional marketization degree ( Market ), R&D expenditure ( RD ), the ratio of independent directors ( Inde ), and management expense ratio ( ME ) as control variables in Equation 1.…”
Section: Robustness Testmentioning
confidence: 99%